Chinese Herbal Formulas and Renal Fibrosis: An Overview - Shen, Yu-Li; Wang, Su-Juan; Rahman, Khalid; Zhang, Li-Jun; Zhang, Hong (Current Pharmaceutical Design, 2018)
All forms of chronic kidney disease (CKD) eventually lead to renal fibrosis irrespective of its origin. It is generally characterized by an excessive accumulation and deposition of extracellular matrix (ECM) and to date, no ideal treatment has been established. Bian-Zheng-Lun-Zhi (syndrome differentiation and treatment), a classic feature of traditional Chinese Medicine (TCM), is a unique method used to diagnose and treat the pathology of a disease. Zheng (syndrome) is used to demonstrate the nature of a disease completely in an extensive and specific manner. Chinese herbal formulas are determined according to TCM theory and this review highlights these formulas and suggests a possible mechanism for their use in the treatment of renal fibrosis.
Keywords: Bian-Zheng-Lun-Zhi